2011
DOI: 10.1179/1743282010y.0000000023
|View full text |Cite
|
Sign up to set email alerts
|

Detecting herbivory in two mosses from an Atlantic Forest, Brazil

Abstract: We recorded evidence for herbivory in the mosses Hypopterygium tamarisci and Lopidium concinnum in a tropical rainforest (Sã o Paulo State, Brazil). We described this herbivory quantitatively, measured the protein and phenol abundance, and identified potential herbivores in the laboratory. We sampled plants from 10 colonies of each species in the years 2007 and 2008. To quantify herbivory, we used an index of damage (ID), with six categories of injury from 0 (0%) to 5 (50-100%). Air-dried moss samples were wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The known accounts of the feeding habits of lepidopteran larvae suggested that only the following four families are known to consume bryophyte capsules: Micropterygidae (Gerson, 1969), Mnesarchaeidae (Grehan, 1984), Lithosiidae (Liu, 1989), and Geometridae (Maciel-Silva & dos Santos, 2011). Thus, this is the first record of Noctuidae larvae that feed on mosses.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The known accounts of the feeding habits of lepidopteran larvae suggested that only the following four families are known to consume bryophyte capsules: Micropterygidae (Gerson, 1969), Mnesarchaeidae (Grehan, 1984), Lithosiidae (Liu, 1989), and Geometridae (Maciel-Silva & dos Santos, 2011). Thus, this is the first record of Noctuidae larvae that feed on mosses.…”
Section: Discussionmentioning
confidence: 88%
“…Although many lepidopteran larvae eat mosses at all latitudes (Prins, 1982;Richardson 1981;Maciel-Silva & dos Santos, 2011), the heavy consumption of H. microphyllum capsules by Agrotis larvae in subtropical cities in spring has never been reported. The known accounts of the feeding habits of lepidopteran larvae suggested that only the following four families are known to consume bryophyte capsules: Micropterygidae (Gerson, 1969), Mnesarchaeidae (Grehan, 1984), Lithosiidae (Liu, 1989), and Geometridae (Maciel-Silva & dos Santos, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1964, Ehrlich and Raven stated that among herbivorous lepidopteran larvae, none is known to feed on bryophytes, nor on ferns, before mentioning the fern eaters Papaipema moths (Noctuidae; see page 598 in Ehrlich & Raven, 1964 ). Years later, studies on early land plants reported that various herbivores, including mammals, birds, gastropods, and arthropods can actually feed on bryophytes (Davidson et al, 1990 ; Fang & Zhu, 2013 ; Glime, 2017 ; Maciel‐Silva & Santos, 2011 ; Singer & Mallet, 1986 ) and pteridophytes (Hamm & Fordyce, 2016 ; Schneider, 2016 ). Some insects have even been shown to specialize on mosses, like weevils from the tribe Ectemnorhinini (Coleoptera: Curculionidae; Chown, 1990 ), larvae of some snipe flies (Diptera: Rhagionidae; Imada & Kato, 2016 ), or crane flies species (Diptera: Tipulidae; Freeman, 1967 ).…”
Section: Introductionmentioning
confidence: 99%